Perbandingan Tonase Kemajuan Tambang Menggunakan Metode Mine Survey Terhadap Realisasi Penambangan di Bukit Everest PT. Antam Tbk. UBPN Sulawesi Tenggara - Sahrul Poalahi Salu; Chanro Silaban (G-Tech: Jurnal Teknologi Terapan, 2024)
Mount Everest, one of PT's mining areas. ANTAM Tbk. UBPN Southeast Sulawesi. To find out the actual mining tonnage, it is done in two ways, namely the weighing method and the truck counting method. The weighing method is applied to high-grade saprolite ore (HGSO) material with Ni content ≥ 1.80%, while the truck counting method is applied to two materials, namely low-grade saprolite ore (LGSO) with a content of 1, 50% ≤ Ni < 1.80% and overburden material (OB). This survey was conducted to compare the actual mining tonnage with the mining progress tonnage using the Mine Survey method. Calculation of the tonnage of the mine survey using the Surpac 6.3 software. Based on the results of the calculations carried out, the difference in the tonnage produced between the mining realization using the mine survey method, namely high-grade saprolite ore and low-grade saprolite ore material, shows that the actual mining tonnage is larger than that of the mine survey method of tailings material is that determined by the mine survey method Tonnage higher than the mining realization.